2013
DOI: 10.1080/17450128.2013.764476
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect among orphaned children and youth living in extended families in sub-Saharan Africa: What have we learned from qualitative inquiry?

Abstract: Researchers and aid organizations have reported that orphans in sub-Saharan Africa (SSA) are particularly vulnerable to abuse and neglect. This article is a review of qualitative studies that address experiences of maltreatment among orphaned children and youth living in extended families in SSA. It aims to inform policy and programming by providing a better understanding of the types of maltreatment encountered and the perceived risk factors. A literature search was carried out using Google, PubMed, Scholars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 60 publications
2
58
1
1
Order By: Relevance
“…Other research has also shown a similar link between being abandoned orphans and turning to the street (Evans, 2005). Orphanhood did not indicate a higher level of violence, in contrast to earlier research from SubSaharan Africa which showed that orphans in general, especially paternal orphans, had a higher risk of violence (Nichols et al, 2014;Morantz et al, 2013). Many of the children who decided to leave home did it due to mistreatment which might explain the difference in result (Olsson, 2016;Benitez, 2007).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Other research has also shown a similar link between being abandoned orphans and turning to the street (Evans, 2005). Orphanhood did not indicate a higher level of violence, in contrast to earlier research from SubSaharan Africa which showed that orphans in general, especially paternal orphans, had a higher risk of violence (Nichols et al, 2014;Morantz et al, 2013). Many of the children who decided to leave home did it due to mistreatment which might explain the difference in result (Olsson, 2016;Benitez, 2007).…”
Section: Discussioncontrasting
confidence: 45%
“…c o m / l o c a t e / c h i l d y o u t h 2016). Earlier research from Sub-Saharan Africa has shown that being an orphan can be associated with a higher risk of being subjected to violence (Morantz et al, 2013, Nichols et al, 2014.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…While some researchers have found significant impacts on test scores (Baird et al, 2011), the present finding is consistent with another orphan study using a standardized national test (Iritani et al, 2016). Orphaned youth may not be able to take full advantage of learning while attending school due to their lack of emotional support or even abuse by their caregivers and low educational expectations (Coneus, Mülenweg, & Stichnoth 2014; Evans 2002; Goldberg & Short 2012; Morantz et al, 2013; Ng’weshemi et al, 2002). In addition, unstable housing, caring for sick caretakers, taking on adult responsibilities at home, or other disadvantages that orphan youth face may contribute to their poor performance (Carrol & Boker 2003).…”
Section: Discussionmentioning
confidence: 99%
“…5860 Conversely, although the evidence is inconsistent, 61,62 some data indicate that youth who are fostered out to extended family (a common practice throughout Africa 63 ) may experience lower levels of behavioral control, relationship quality and financial support, and may experience more conflict with household adults, than youth who reside with biological parents, resulting in lower levels of well-being. 64,65 Other evidence, however, suggests that the effects of child fosterage may be more complex and may depend on the specifics of the fostering arrangement and the circumstances surrounding it. 62 For example, families that have fewer financial resources may be less able to provide financial support to their youth or to keep them in school.…”
mentioning
confidence: 99%